Visceral Leishmaniasis Patients Display Altered Composition and Maturity of Neutrophils as well as Impaired Neutrophil Effector Functions - Yizengaw, Endalew; Getahun, Mulusew; Tajebe, Fitsumbrhan; Cruz Cervera, Edward; Adem, Emebet; Mesfin, Getnet; Hailu, Asrat; Van der Auwera, Gert; Yardley, Vanessa; Lemma, Mulualem; Skhedy, Ziv; Diro, Ermias; et al. (Frontiers in Immunology, 2016)
Immunologically, active visceral leishmaniasis (VL) is characterised by profound immunosuppression, severe systemic inflammatory responses and an impaired capacity to control parasite replication. Neutrophils are highly versatile cells, which play a crucial role in the induction as well as the resolution of inflammation, the control of pathogen replication and the regulation of immune responses. Neutrophil functions have been investigated in human cutaneous leishmaniasis, however, their role in human visceral leishmaniasis is poorly understood. In the present study we evaluated the activation status and effector functions of neutrophils in patients with active VL and after successful anti-leishmanial treatment. Our results show that neutrophils are highly activated and have degranulated; high levels of arginase, myeloperoxidase and elastase, all contained in neutrophils’ granules, were found in the plasma of VL patients. In addition, we show that a large proportion of these cells are immature. We also analysed effector functions of neutrophils that are essential for pathogen clearance and show that neutrophils have an impaired capacity to release neutrophil extracellular traps, produce reactive oxygen species and phagocytose bacterial particles, but not Leishmania parasites. Our results suggest that impaired effector functions, increased activation and immaturity of neutrophils play a key role in the pathogenesis of VL.